Consumer value co-creation in online communities: What is the consumer's motivation for participating and contributing in an online community? - Kertbo, Kia (2008)
There are increasing calls amongst the academic community that a new marketing logic is needed for the 21st century. In contrast to more autonomous approaches adopted by companies in the past, this new marketing logic is marked by a co-creation of value process involving both consumers and manufacturers. In this light online communities have been identified as valuable platforms in which members engage in value-creating activity which companies can integrate into their new product development processes.